The hemoglobin glycation index predicts the risk of adverse cardiovascular events in coronary heart disease patients with type 2 diabetes mellitus - Xu, Shuai; Qin, Zhen; Yuan, Ruixia; Cui, Xiaolin; Zhang, Li; Bai, Jing; Liu, Gangqiong; Wang, Zeyu; Yu, Fengyi; Lv, Yan; Zhang, Jinying; Tang, Junnan (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have shown that the hemoglobin glycation index (HGI) can be used as a predictor of diabetic complications. However, limited information is currently available to indicate the correlation between HGI and comorbidity of coronary heart disease (CHD) and diabetes. This study aimed to evaluate the potential of HGI to predict major adverse cardiovascular events (MACEs) in CHD patients with type 2 diabetes mellitus (T2DM). Method: A total of 918 CHD patients with T2DM were enrolled in a 3-year retrospective cohort study, from December 2017 to December 2020 at the First Affiliated Hospital of Zhengzhou University. Data including fasting blood glucose(FPG/FBG) and glycated hemoglobin A1c(HbA1c) were collected. HGI was calculated as actual measured HbA1c minus predicted HbA1c. Based on the linear relationship between FPG and HbA1c, the formula was calculated as: predicted HbA1c=0.459×fasting blood glucose（FPG）+ 4.532. Three groups were further divided based on the levels of HGI levels, including low, medium, and high levels. Result: Kaplan Meier analysis indicated that elevated HGI was strongly associated with MACE (log-rank P < 0.001). Multivariate Cox regression analysis revealed that elevated HGI was an independent risk factor for incident MACE in CHD patients with T2DM (adjusted hazard ratio(HR): 1.546; 95% confidence interval(CI): 1.439-1.661, P<0.001) Conclusions: HGI is an independent predictor of MACE events in CHD patients with T2DM, and high HGI indicates a higher risk of MACE occurrence.